1-Phenyl-1-[(1-phenylethyl)sulfonylmethylsulfonyl]ethane - Jing-tao Liu; Yan-ji Wang; Feng-xia Sun; Huai-ping Kang; Xiang-min Chen; Bing-zhu Zhang; De-bin Wang (Acta Crystallographica Section E, 2009)
There are two molecules in the asymmetric unit of the title compound, C17H20O4S2. There are slight differences in the twist of the two rings relative to the S–C–S chain [dihedral angles of 48.41 (18) and 87.58 (16)° in the first molecule and 45.98 (18) and 87.02 (18)° in the second] and the difference in the C—S—C—S torsion angles [176.68 (17) and −77.6 (2)° for the two independent molecules].